Evaluation of critical patients with suspected sepsis in a university hospital (Research, Society and Development, 2021)
Sepsis is a major cause of death in critically ill patients. Rapid and adequate antibiotic therapy is of great importance for these patients, but long-term antimicrobial treatments are undesirable because they increase resistance to antibiotics. This research aims to evaluate the clinical and epidemiological data of critically ill patients with suspected sepsis in a University Hospital in the interior of Sergipe. A prospective, quantitative and descriptive longitudinal exploratory epidemiological study was carried out in the critical units of the Hospital Universitário de Lagarto (Sergipe - Brazil). The research was approved by the institutional review board - CAAE Ethics Committee No. 16847919.8.0000.5546 - Opinion number: 3,496,684 - from the Federal University of Sergipe Foundation (UFS). 48 patients were followed through an active daily search for new suspected cases of sepsis. As for the results, 52.1% (25) of the patients were women, with a mean age of 64.29 years. The average length of hospital stay was 32.02 days. More than half of the suspected cases of sepsis, 52.1% (25) were secondary to pulmonary and respiratory tract infections and 22.9% (11) related to the urinary focus. The most prescribed antimicrobial treatments were: 21.3% Meropenem; 13.9% Piperacillin + Tazobactam; 13.1% Ceftriaxone. Of the total number of patients evaluated, 45.8% (22) died. It is concluded that patients with prolonged periods of hospitalization are more vulnerable to sepsis. As a result, the mortality rate identified is worrying and reinforces the need to early identify the factors associated with the development of sepsis and, therefore, the importance of implementing a sepsis protocol in institutions.